Wakaf Tunai dalam Perspektif Ulama Mujtahid - Moh Hatta (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
In this modern age, one of the forms and movements of endowments that attracted the attention of scholars and scholars is cash waqf. In Islamic history, cash waqf developed well in the days of the Bani Mamluks and Ottoman Turks. Basically wakaf is an instrument maliyah, so wakaf not only serves as a mere ritual worship but also social function. Waqf is a form of a steady expression of faith and a high sense of solidarity among fellow human beings, so it is an attempt to manifest and maintain vertical relationships (hablun min Allah) and horizontal relationships (hablun min al-nas). In the context of Indonesia, the enactment of the Law of the Republic of Indonesia no. 41 of 2004 on Wakaf directed to empower wakaf which is one of the instruments in building the socio-economic life of Muslims. The presence of Wakaf Law is a momentum of wakaf empowerment productively. In this paper will be elaborated discussion of waqf in general, followed discussion of cash waqf, as well as views of the mujathid cleric about cash waqf.